2003
DOI: 10.1007/s00127-003-0685-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in healthy old age: relationships with childhood IQ, minor psychological symptoms and optimism

Abstract: In the absence of dementia, childhood IQ, HADS and LOT explain 26.9% of the variance in QoL as reported by community-resident old people. The direction of association between current anxiety and depressive symptoms and lower QoL is uncertain. Lower childhood IQ may contribute to coping less well with later life. Lower QoL is not an invariable concomitant of mild cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 14 publications
3
46
1
1
Order By: Relevance
“…Depressive mood state plays a particularly important role in these groups, as does the personality trait Emotional Stability, both of which corroborate previous research [6,32]. A degree of caution is needed here, however, as the strong association between mood state and the Emotional Stability trait suggests they may well be measuring a similar construct, sometimes called negative affectivity [62].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Depressive mood state plays a particularly important role in these groups, as does the personality trait Emotional Stability, both of which corroborate previous research [6,32]. A degree of caution is needed here, however, as the strong association between mood state and the Emotional Stability trait suggests they may well be measuring a similar construct, sometimes called negative affectivity [62].…”
Section: Discussionsupporting
confidence: 82%
“…Social class did play a part in predicting some aspects of QoL in both groups; however, as this was occupation-based, it could be a reflection of their current financial circumstances. The lack of association between childhood cognitive ability and QoL in the LBC1921 regression analyses contradicts Bain et al's findings in a similar cohort [6] but mirrors the findings of Gow et al [60], who reported that satisfaction with life in this group was unrelated to childhood IQ. However, there were bivariate associations between childhood IQ and the environment and social domains in the LBC1921, and with physical, environment and general QoL in the LBC1936.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations